Long‐term photo‐id and satellite tracking reveal sex‐biased survival linked to movements in an endangered species. Issue 7 (30th March 2020) - Schofield, Gail; Klaassen, Marcel; Papafitsoros, Kostas; Lilley, Martin K. S.; Katselidis, Kostas A.; Hays, Graeme C.
Abstract: Sex‐biased survival linked to anthropogenic threats places populations at risk. We show the utility of long‐term multidecadal photo‐identification (photo‐id) combined with long‐term high‐resolution (Fastloc‐GPS) satellite telemetry to investigate the links between mortality rates and patterns of movement for a wide‐ranging, endangered marine vertebrate. Using a photo‐identification database of 947 loggerhead turtles ( Caretta caretta ) compiled over 18 yr, we estimated greater annual survival rates of females (0.89; 95% confidence interval [CI] 0.87–0.90) compared to males (0.73; 95% CI 0.67–0.78). For males satellite‐tracked across multiple breeding seasons, 100% (26 of 26) returned to the same breeding site, suggesting the calculated lower male survival rate was likely not due to emigration to breed elsewhere. 10, 111 and 2, 524 tracking days for males ( n = 39 individuals) and females ( n = 18 individuals), respectively, revealed different habitat‐use patterns outside the breeding season: males tended to occupy foraging sites closer to shore and closer to breeding sites but, due to their generally annual breeding, compared to biennial breeding for females, males migrated further per year on average. These differences in movement patterns likely contribute to higher mortality in males through increased interaction with anthropogenic threats. Long‐term identification coupled with tracking offers great promise for estimating the survival rates of other wide‐ranging species.